THE POPULATION’S ATTITUDE TO THE PROBLEM OF THE INFLUENCE OF EDUCATION AND SCIENCE ON SOCIETY - Natalia V. Mayorova (Статистика и экономика)
The article is devoted to the analysis of attitudes toward the future of education in the conditions, when it is practically not considered as priorities for further socio-economic development. However, Russians do not consider education to symbols of national prestige, including taking into account the structure of the employed in the economy according to the criteria received specialty. At the same time, the vast majority of the population sees and evaluates the impact of science and technology on life. Accordingly, the rationale behind the necessity of forming a new system of economic relations, adequate to the requirements of the knowledge society.